Phenolics, rather than glucosinolates, mediate host choice of Bemisia tabaci MEAM1 and MED on five cabbage genotypes. (27th January 2020) - Yang, Jinjian; Xie, Wen; Liu, Baiming; Wang, Shaoli; Wu, Qingjun; He, Yuchi; Zhang, Youjun; Jiao, Xiaoguo
Abstract: Worldwide, the most two important cryptic species of Bemisia tabaci (Gennadius) (Hemiptera: Aleyrodidae) are MEAM1 (Middle East–Asia Minor 1, "B" biotype) and MED (Mediterranean, "Q" biotype). Although both B. tabaci MEAM1 and MED are polyphagous, they differ greatly in host choice and performance on various host plants. MEAM1 prefer to settle and perform better than MED on cabbage ( Brassica oleracea ), for example, but the underlying mechanism is largely unexplored. In the present study, we first measured the contents of the main secondary insect‐resistant substances (glucosinolates and phenolics) and main nutrients (soluble proteins, total amino acids and total nitrogen) in five cabbage genotypes. We then examined the settling and oviposition choices of MEAM1 and MED on the five cabbage genotypes, respectively. The settling and oviposition preferences of both MEAM1 and MED were negatively related to the content of total phenolics rather than to the content of glucosinolates or main nutrients. Furthermore, our results showed that MEAM1 ranked the host quality of the cabbage genotypes more accurately than MED. The results at least in part indicate that total phenolics rather than glucosinolates mediate the host choice of B. tabaci MEAM1 and MED on the five cabbage genotypes.